Answer:
-6
Step-by-step explanation:
(2x + 4) – (3x + 6)
Distribute the minus sign
2x +4 -3x -6
-x -2
Let x = 4
-4-2
-6
Answer:
-6
Step-by-step explanation:
(2x + 4) – (3x + 6) =
= 2x + 4 - 3x - 6
= -x - 2
= -(4) 2
= -6
Solve for z.
–9 + 8(14z + 2) = 7(17z + 8)
z =
Answer:
z=-7
Step-by-step explanation:
-9+8*14z+8*2=7*17z+7*8
-9+112z+16=119z+56
112z+7=119z+56
-112z -112z
7=7z+56
-56 -56
-49=7z
:7 :7
z=-7
Answer:
[tex] \boxed{z = -7} [/tex]
Step-by-step explanation:
[tex] = > - 9 + 8(14z + 2) = 7(17z + 8) \\ \\ = > - 9 + (8 \times 14z + 8 \times 2) = (7 \times 17z) + (7 \times 8) \\ \\ = > - 9 + 112z + 16 = 119z + 56 \\ \\ = > 7 + 112z = 119z + 56\\ \\ = > 7 + 112z - 119z = 56 \\ \\ = > 7 - 7z = 56 \\ \\ = > - 7z = 56 - 7 \\ \\ = > - 7z = 49 \\ \\ = > 7z = - 49 \\ \\ = > z = - \frac{49}{7} \\ \\ = > z = - 7[/tex]
What is the value of y?
Answer:
option a
Step-by-step explanation: y+y=114 (exterior angle property)
2y=114
y =114/2
y = 57
The measure of angle 'y' in the triangle is 57 degrees.
What is the measure of y in the triangle?The figure in the image is a triangle.
From the diagram:
Angle 1 = y degrees
Angle 2 = y degrees
Angle 3 =?
First, we determine the measure of the third angle.
Since the sum of angles on a straight line equals 180 degrees:
Angle 3 + 114 = 180
Angle 3 = 180 - 114
Angle 3 = 66
Now, the total sum of the interior angles of a triangle equals 180 degrees.
Hence:
Angle 1 + Angle 2 + Angle 3 = 180
y + y + 66 = 180
Collect and add like terms:
2y + 66 = 180
2y = 180 - 66
2y = 114
Divide both sides by 2:
y = 114/2
y = 57°
Therefore, y has a value of 57.
Option A) 57° is the correct answer.
Learn more about the interior angles of triangles here: https://brainly.com/question/33265804
#SPJ2
can someone explain the process i have to take?
Answer:
x = 76
Step-by-step explanation:
PQ is a tangent to the circle at Q , thus the angle between the tangent and the radius is 90°
The sum of the 3 angles in the triangle = 180°, thus
x = 180° - (90 + 14)° = 180 - 104 = 76
jaskson kitten weghed 2 pound
umm what the rest of the question
Answer:
no he weghed 3 pound
Step-by-step explanation:
What is the true solution to ln 20 + ln 5 = 2 ln x ?
x=5
x=10
x=50
x=100
Answer:
ln(20×5)=InX^2
In100=InX^2
X^2=100
X=10
The solution of the given expression will be x = 10
What is an expression?
Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division.
The solution of the given equation is:-
ln( 20 × 5) = InX²
In100 = InX²
X² = 100
X = 10
Therefore the solution of the given expression will be x = 10
To know more about expression follow
https://brainly.com/question/723406
#SPJ2
Which system of inequalities is graphed below?
Answer: It’s A y > x^2-4
Y < x^2+3
Step-by-step explanation:
f(x) = 3x5 - 9x3 - 19x2 - 50; k= 2
Answer:
-102 i think. sorry if i am wrong
Step-by-step explanation:
Find the sum of the first 34 terms to the nearest integer
13,19,25
Answer:
3808
Step-by-step explanation:
Given the sequence: 13,19,25
First Term, a=13
Common Difference, d=19-13=25-19=6
Since we have a common difference, the sequence is an arithmetic sequence.
We determine the sum of any nth term of an arithmetic sequence using the formula:
[tex]S_n=\frac{n}{2}[2a+(n-1)d] \\n=34, a=13, d=6\\$Therefore:\\S_{34}=\frac{34}{2}[2(13)+(34-1)*6]\\=17[26+33*6]\\=17[26+198]\\=17*224\\S_{34}=3808[/tex]
The sum of the first 34 terms is 3808.
Which equation is equivalent to (2x^2+4x-7)(x-3)
Answer:
2 x^3 - 2 x^2 - 19 x + 21
Step-by-step explanation:
Expand the following:
(2 x^2 + 4 x - 7) (x - 3)
Hint: | Multiply out (x - 3) (2 x^2 + 4 x - 7).
| | 2 x^2 | + | 4 x | - | 7
| | | | x | - | 3
| | -6 x^2 | - | 12 x | + | 21
2 x^3 | + | 4 x^2 | - | 7 x | + | 0
2 x^3 | - | 2 x^2 | - | 19 x | + | 21:
Answer: 2 x^3 - 2 x^2 - 19 x + 21
Use long division to find the quotient below.
(x2 + 3x - 18) + (x-3)
Answer:
6x-21
Step-by-step explanation:
In which quadrant does the point (-5, -21) lie? A. Quadrant IV B. Quadrant I C. Quadrant III D. Quadrant II
Answer:
Quadrant 3
Step-by-step explanation:
Answer:
Quadrant 3
Step-by-step explanation:
All negatives all fall under 3
Solve for f.
–7f − 9 = 9 − 4f
f =
Answer:
[tex] \boxed{f = -6} [/tex]
Step-by-step explanation:
[tex] = > - 7f - 9 = 9 - 4f \\ \\ = > - 7f + 4f - 9 = 9 \\ \\ = > - 3f = 9 + 9 \\ \\ = > - 3f = 18 \\ \\ = > 3f = - 18 \\ \\ = > f = - \frac{18}{3} \\ \\ = > f = - 6[/tex]
Drilon got 63 out of 72 correct in his test. What fraction of the marks did he get correct?
Answer:
87.5%
Step-by-step explanation:
Answer:
7/8 or 87.5%
Step-by-step explanation:
Total= 72
Correct= 63
Fraction of correct marks= 63/72= 7*9/8*9= 7/8 or 87.5%
2 Points
If two chords in a circle are congruent, then they are
A. perpendicular
B. the same distance from the center of the circle
C. parallel
If two chords in a circle are congruent, then they are the same distance from the center of the circle. Then the correct option is B.
What is a circle?It is the close curve of an equidistant point drawn from the center. The radius of a circle is the distance between the center and the circumference.
The central angle is double the angle at the periphery that was subtended by the same chords.
Both the extreme points of the chords are connected to the circle. Then the two triangles are formed whose two sides are the radius of the circle that is congruent to each other. Then the triangle will be an isosceles triangle.
And the chord length is also congruent. Then the triangles are congruent to each other by SSS postulates.
If two chords in a circle are congruent, then they are the same distance from the center of the circle. Then the correct option is B.
More about the circle link is given below.
https://brainly.com/question/11833983
#SPJ5
pls help for the brainliest
Answer:
[tex]12.92cm^2[/tex]
Step-by-step explanation:
[tex]A=\frac{h_bb}{2} \\=\frac{3.4*7.6}{2} \\12.92cm^2[/tex]
Answer:
12.92 cm²
Step-by-step explanation:
The area (A) of a triangle is calculated as
A = [tex]\frac{1}{2}[/tex] bh ( b is the base and h the perpendicular height )
Here b = 7.6 and h = 3.4 , thus
A = [tex]\frac{1}{2}[/tex] × 7.6 × 3.4 = 3.8 × 3.4 = 12.92 cm²
how would you do this
Answer:
16cm^2
Step-by-step explanation:
Count all of the whole squares 1st
the do the ones at the sides
Answer: 16 units squared
If there is units for the grid, use those as your measurements, but if not, use each box to equal 1.
You can solve this by finding the area of a rectangle bigger than the original shape (straighten out diagonal lines)
Once you do this, count the units (boxes) of the length and width of the rectangle (5 X 4)
You would then multiply the length and width to find the area of the rectangle
5 * 4 = 20
..... But you still need to find the parallelogram so you have to subtract the space you filled in
Since the shape is a parallelogram, you can tell that the area filled in is equal on both sides, and when put together, they form a smaller rectangle
This rectangle would be 1 X 4
1 * 4 = 4
Then you have to subtract the smaller rectangle from the larger rectangle
20 - 4 = 16
The question is below, will give brainlist.
Answer:
[tex]\boxed{\sf \ 48 \ }[/tex]
Step-by-step explanation:
Hello,
the sum of all angles of the triangle at the left must be 180
so the last one is 180 - 80 - 60 = 40
and then the angle at the bottom left of the second triangle is 180 - 40 -72 = 180 - 112 = 68
and then the angle that we have to find is 180 - 64 - 68 = 48
hope this helps
Put the following equation of a line into slope-intercept form, simplifying all fractions. 12x+2y= -12
Answer:
y = -6x - 6
Step-by-step explanation:
First, subtract 12x from both sides:
12x + 2y = -12
-12x -12x
-----------------------
2y = -12x - 12
Divide both sides by 2:
y = -6x - 6
Answer:
y=−6x−6 because thats what the guy on top of me said
Step-by-step explanation:
The standard form of the equation of a parabola is y= x2 - 6x + 14.
What is the vertex form of the equation?
O A. y= (x-3)2 + 23
O B. y=(x-3)2 + 5
ed
O c. y=(x-3)2 + 15
O D. y= (x+3)(x-3) + 5
Answer:
Let's begin by looking at the standard form for the equation of a parabola. The standard form is (x - h)2 = 4p (y - k), where the focus is (h, k + p) and the directrix is y = k - p.
Step-by-step explanation:
hope this helps you :)
) If (7-3)2 x 7x+4 = 77, find the value of x.
Answer:
Solve for x:
56 x^2 + 4 = 77
Subtract 4 from both sides:
56 x^2 = 73
Divide both sides by 56:
x^2 = 73/56
Take the square root of both sides:
Answer: |
| x = sqrt(73/14)/2 or x = -sqrt(73/14)/2
On a piece of paper, graph f(x)= 2 if 2 < x ≤ 4 4 if 4 < x ≤ 6 6 if 6 < x ≤ 8 Then determine which answer choice matches the graph you drew (IM HORRIBLE AT THIS PLEASE HELP)
Answer:
Graph A
Step-by-step explanation:
I graphed each of the inequalities on separate graphs below. When all the graphs are put together, they match Graph A.
The choice that matches the graph of the function as is defined to Graph A.
How to find the function which was used to make graph?There are many tools we can use to find the information of the relation which was used to form the graph.
A graph contains data of which input maps to which output.
Analysis of this leads to the relations which were used to make it.
The given function are;
f(x)= 2 ,if 2 < x ≤ 4
f(x)= 4, if 4 < x ≤ 6
f(x)= 6 ,if 6 < x ≤ 8
This means that how we get the staircase pattern as shown in graph A. This is considered a piecewise function since we're graphing pieces of various other functions.
Hence, The choice that matches the graph of the function as is defined to Graph A.
Learn more about finding the graphed function here:
https://brainly.com/question/27330212
#SPJ5
What is the surface area of the triangular prism shown?
Answer:
[tex]A=2\times5\times 10+6\times10+2\times\frac{6\times4}{2} =184\;cm^2[/tex]
Write an equation of a line that passes through the following two points: (4,-6) and (2,8).
Answer:
y=-7x+22
Step-by-step explanation:
Triangles E F G and E prime F prime G prime are shown. Angles F E G and F prime E prime G prime are 72 degrees. Angles E F G and E prime F prime G prime are 66 degrees. What additional information could be used to prove ΔEFG ΔE'F'G' using AAS? Check all that apply.
Answer:
We need a non-included side of one triangle
Step-by-step explanation:
By means of the AAS postulate.
The Angle-Angle-Side postulate (AAS) tells us that if two angles and a non-included side of one triangle are congruent to two angles and the corresponding non-included side of another triangle, then the two triangles are congruent.
Answer:1, 2, 5
Step-by-step explanation:
just did it on edge
Eight less than a third of a number is the sum of that number and one.
Answer:
[tex]x = -13\frac{1}{2}[/tex]
Step-by-step explanation:
Eight less than a third of a number is the sum of that number and one.
Let the number be x.
That is:
[tex]\frac{1}{3}x - 8 = x + 1\\ \\=> x - \frac{1}{3}x = -8 - 1 \\\\\frac{2}{3}x = -9\\\\x = -9 * \frac{3}{2}\\ \\x = \frac{-27}{2}[/tex]
[tex]x = -13\frac{1}{2}[/tex]
A circle is centered at I(0,0). The point T(5,8) is on the circle.
Where does the point Z(-[tex]-\sqrt{15}, \sqrt{74}[/tex] lie?
Answer:
Also on the circle
Step-by-step explanation:
solved it graphically with desmos.
please press brainliest ((gives you 10 points back btw)
5-7y/2+4y equals -8/7
Answer:
[tex] \boxed{y = 3} [/tex]
Step-by-step explanation:
[tex] = > \frac{5 - 7y}{2 + 4y} = - \frac{8}{7} \\ \\ = > 7(5 - 7y) = - 8(2 + 4y) \\ \\ = > (7 \times 5) - (7 \times 7y) = ( - 8 \times 2) + ( - 8 \times 4y) \\ \\ = > 35 - 49y = - 16 - 32y \\ \\ = > 35 - 49y + 32y = - 16 \\ \\ = > 35 - 17y = - 16 \\ \\ = - 17y = - 16 - 35 \\ \\ = > \cancel{- }17y = \cancel{- } 51 \\ \\ = > 17y = 51 \\ \\ = > y = \frac{51}{17} \\ \\ = > y = 3[/tex]
f(x) = x ^ 2 + 6x - 4 in vertex form
Answer:y=(x-6)^2-4
Step-by-step explanation:
Answer:
f(x) = (x + 3)² - 13
Step-by-step explanation:
The equation of a parabola in vertex form is
f(x) = a(x - h)² + k
Given
f(x) = x² + 6x - 4
Using the method of completing the square
add/subtract ( half the coefficient of the x- term )² to x² + 6x
f(x) = x² + 2(3)x + 9 - 9 - 4
f(x) = (x + 3)² - 13 ← in vertex form
what is the midpoint of the segment shown below
Answer:
(-1, -1/2)
Step-by-step explanation:
To find the x coordinate of the midpoint, add the x coordinates and divide by 2
( -11+9)/2 = -2/2 = -1
To find the y coordinate of the midpoint, add the y coordinates and divide by 2
(0+-1)/2 = -1/2
(-1, -1/2)
What is the constant of proportionality in the equation y = StartFraction x over 9 EndFraction?
Answer:
1/9
Step-by-step explanation:
I'm assuming the equation you mean is y = (x/9) -- if so, parentheses aren't really required.
The equation for the constant of proportionality is y=kx. So, we will want to find the value of k, which is the constant. The y and x variables are in both equations already, and there is only the 1/9, which is k.
Therefore, the constant of proportionality is 1/9. We can check this answer by putting 1/9 back into the equation. y = 1/9 (x) or y= x/9.
Answer:
1/9
Step-by-step explanation:
None. Just trust me.